Integrated motor drive for vehicle electrification: a step toward a more sustainable and efficient transportation system - Tole Sutikno; Sanjeevikumar Padmanaban (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The transportation sector is a big source of greenhouse gas (GHG) emissions. It is responsible for about 20% of all carbon dioxide (CO2) emissions in the world, and most of those emissions come from road transportation. The development of greater efficiency vehicles with much reduced fuel consumption and GHG emissions is critical for vehicle electrification and a sustainable transportation system. Electric vehicles (EVs) offer higher energy efficiency than internal combustion engines and emit no CO2 during operation. For future vehicle electrification, cost-effective electric powertrain options are required. The current state of development of two major components of the EV powertrain: motors and drives, is introduced in this editorial.